2012
DOI: 10.1111/j.1472-765x.2012.03203.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an optimized random amplified polymorphic DNA protocol for fingerprinting of Klebsiella pneumoniae

Abstract: Aims:  To develop an optimized random amplified polymorphic DNA (RAPD) protocol for fingerprinting clinical isolates of Klebsiella pneumoniae. Methods and Results:  Employing factorial design of experiments, repeatable amplification patterns were obtained for 54 nosocomial isolates using 1 μmol 1−1 primer, 4 mmol 1−1 MgCl2, 0·4 mmol 1−1 dNTPs, 2·5 U Taq DNA polymerase and 90 ng DNA template in a total volume of 25 μl. The optimum thermocycling program was: initial denaturation at 94°C for 4 min followed by 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Genetic profiles of the isolates by RAPD, confirmed by PFGE have been reported in our previous article (7). Presence of bla ESBL genes ( bla SHV , bla TEM and bla CTX-M ) and the sequencing result for the isolates were also previously reported (9).…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…Genetic profiles of the isolates by RAPD, confirmed by PFGE have been reported in our previous article (7). Presence of bla ESBL genes ( bla SHV , bla TEM and bla CTX-M ) and the sequencing result for the isolates were also previously reported (9).…”
Section: Methodssupporting
confidence: 77%
“…Genetic profiles of the isolates by RAPD (Figure 2) which were confirmed by PFGE, showed six major clusters (a-f) on a similarity level of 70%, and 21 different groups on a similarity level of 85% (7). Characterization of bla ESBL genes from our previous work showed that 27 isolates (77.1%) harbored bla SHV genes including bla SHV-12 , bla SHV-5 and bla SHV-11 , 17 (48.6%) carried bla TEM genes characterized as bla TEM-1 by sequencing, 16 (45.71%) carried bla CTX-M-I which belonged to bla CTX-M-15 and 10 (28.57%) contained bla CTX-M-III characterized as bla CTX-M-8 (9).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…RAPD-PCR was chosen because it is a rapid and simple method which when optimized has proven competitive with the gold standard of pulse field gel electrophoresis [26, 27]. RAPD1, also referred to as Primer 640 by other authors [13, 26], proved to be optimal for DNA fingerprinting since it allowed the clear distinction of DNA banding patterns for all of the isolates tested. The resulting RAPD profiles for this select group of isolates showed that there was diversity among those isolated during 2008–2010 and those recovered in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were initially screened for RAPD typing using five different primers: RAPD1 (5′-CGTGGGCCT), RAPD2 (5′-TCGTCGGCGT), RAPD3 (5′-GTGACGTAGG), RAPD4 (5′-CTTGAGTGGA), RAPD5 (5′-GAGATGACGA) (Sigma-Aldrich). RAPD–PCR was conducted under reaction conditions described by Ashayeri-panah et al [13]. The amplified products were separated by electrophoresis in a 2.0% agarose gel containing GelRed™ run in 1 × TAE buffer at 65 V for 3 h 30 min until amplified fragments are separated.…”
Section: Methodsmentioning
confidence: 99%